1996
DOI: 10.1152/ajpcell.1996.271.6.c1981
|View full text |Cite
|
Sign up to set email alerts
|

Actin polymerization and depolymerization during apoptosis in HL-60 cells

Abstract: Little is known about the biochemical "machinery" responsible for the morphological features of apoptosis, although the cytoskeleton is presumed to be involved. Using flow cytometry, polyacrylamide gel electrophoresis, and fluorescence microscopy, we show that apoptosis induced by ultraviolet (UV) irradiation or 80 micrograms/ml etoposide correlates with early transient polymerization and later depolymerization of filamentous (F)-actin and dramatic changes in visible microfilament organization. Depolymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
68
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 17 publications
17
68
1
Order By: Relevance
“…21 In addition to the DNA fragmentation, changes to the actin cytoskeleton also implicate the possibility of PCD in the SI response, as the highly sustained actin depolymerization that accompanies SI 17 has been observed in several animal cells undergoing apoptosis. [18][19][20] Our electron microscopy data describing the morphological changes in pollen undergoing the SI response revealed none of the morphological hallmarks that typically characterize necrosis, such as loss of membrane integrity, cellular swelling or rupture. Even though we cannot rule out the possibility of secondary necrosis, our data are not inconsistent with the hypothesis that PCD may occur in SI challenged pollen tubes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition to the DNA fragmentation, changes to the actin cytoskeleton also implicate the possibility of PCD in the SI response, as the highly sustained actin depolymerization that accompanies SI 17 has been observed in several animal cells undergoing apoptosis. [18][19][20] Our electron microscopy data describing the morphological changes in pollen undergoing the SI response revealed none of the morphological hallmarks that typically characterize necrosis, such as loss of membrane integrity, cellular swelling or rupture. Even though we cannot rule out the possibility of secondary necrosis, our data are not inconsistent with the hypothesis that PCD may occur in SI challenged pollen tubes.…”
Section: Discussionmentioning
confidence: 99%
“…17 Intriguingly, long-term F-actin depolymerization has been identified as a feature of apoptosis. [18][19][20] Preliminary data suggesting that a programmed cell death (PCD) signalling cascade may be stimulated in the SI response was provided by evidence that DNA fragmentation, generally considered a hallmark in PCD, is stimulated in SI challenged pollen tubes. 21 This, together with similarities between the P. rhoeas SI system and the hypersensitive response (HR), which triggers a PCD cascade, has led to the idea that PCD may be triggered by the SI response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that actin might be both an apoptotic target and an early modulator of cell commitment to apoptosis (18). Moreover, reorganization of the actin network was proved to be required for plasma membrane blebbing (19,20). There is growing evidence that intact F-actin is required for autophagocytosis, presumably for enabling cells to transport vacuoles to lysosomes (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Different cytoskeleton-disrupting agents, such as cytochalasins B, D and E and latrunculin A, prevent this second round of volume loss, along with DNA degradation and formation of apoptotic bodies. 7,8 In this second stage, both cytochrome c release and caspases seem to be involved and required for AVD (reviewed in Remillard and Yuan 6 ). Yet, a channel-mediated K þ outward movement is activated by cytochrome c independently of initiator caspase-9 activation.…”
mentioning
confidence: 99%